1980
DOI: 10.1001/archderm.116.9.1023
|View full text |Cite
|
Sign up to set email alerts
|

Response of psoriatic nails to oral photochemotherapy

Abstract: Ten patients with generalized psoriasis, which included nail involvement, were treated with total-body oral photochemotherapy. A combination of methoxsalen and high-intensity ultraviolet A radiation was employed and its therapeutic efficacy in nail psoriasis ascertained. Among the ten patients, there were 26 instances of the following nail signs: pitting, onycholysis, "oil drop" change, subungual hyperkeratosis, nail-plate crumbling, proximal nail-fold psoriasis, and onychorrhexis. Of the 26, eighteen improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 0 publications
0
17
1
1
Order By: Relevance
“…Oral PUVA appeared to be quite beneficial in patients who had PNF involvement and nail plate crumbling, 109 while topical PUVA demonstrated its efficacy on isolated cases of pitting and onycholysis. 110 Superficial radiotherapy showed mixed results, as one study documented complete clearance of subungual hyperkeratosis, discoloration, and cracking in 3 patients, with 1 subject in remission for 20 years, 111 while another study showed no improvement for patients suffering from pitting, onycholysis, subungual hyperkeratosis, and destruction of nail plate.…”
Section: Conclusion and Future Trendsmentioning
confidence: 97%
See 1 more Smart Citation
“…Oral PUVA appeared to be quite beneficial in patients who had PNF involvement and nail plate crumbling, 109 while topical PUVA demonstrated its efficacy on isolated cases of pitting and onycholysis. 110 Superficial radiotherapy showed mixed results, as one study documented complete clearance of subungual hyperkeratosis, discoloration, and cracking in 3 patients, with 1 subject in remission for 20 years, 111 while another study showed no improvement for patients suffering from pitting, onycholysis, subungual hyperkeratosis, and destruction of nail plate.…”
Section: Conclusion and Future Trendsmentioning
confidence: 97%
“…108 Although the efficacy of phototherapy and photochemotherapy has been widely validated for treating psoriasis of the skin, there has been a clear absence of evidence pertaining to its value in nail psoriasis therapy. Marx and Scher 109 published J AM ACAD DERMATOL VOLUME 57, NUMBER 1 a prospective study in 1980 in which 10 patients (a total of 26 separate dystrophies), who had generalized psoriasis with nail involvement, were treated with oral photochemotherapy (Table V). The regimen consisted of methoxsalen, at a dose of 0.6 mg/kg, and high intensity UVA radiation, which was administered 2 to 3 times a week.…”
Section: Radiation Therapiesmentioning
confidence: 99%
“…Marx and Scher[79] published a prospective study in 1980 in which 10 patients (a total of 26 separate dystrophies), who had generalized psoriasis with nail involvement were treated with oral photochemotherapy. The regimen consisted of methoxsalen, at a dose of 0.6 mg/kg and high-intensity UVA radiation, which was administered 2-3 times a week.…”
Section: Treatment Of Nail Psoriasismentioning
confidence: 99%
“…Psoralen plus ultraviolet A (PUVA) is one of the most common photochemotherapeutic regimens. The psoralen can be administered orally or topically, and at times, the nails can be soaked in the solution before exposure to ultraviolet A. PUVA appears to be successful in treating psoriasis arising from the nail bed (e.g., onycholysis, subungual hyperkeratosis) but does little to improve some nail matrix disease symptoms (e.g., pitting) [30,31]. …”
Section: Conventional Treatment Approaches To Managing Nail Psoriasismentioning
confidence: 99%